Envisaging agency as discourse hybridity: a Butlerian analysis of secondary classroom discourses. Issue 2 (3rd March 2016) - Charteris, Jennifer
Abstract : Conceptualised from a range of sociological perspectives, and theorised extensively over the last 50 years, human agency is an integral element to lifelong learning. Poststructural theory with its decentred discursive construction of the learner offers a vibrant conception of classroom dynamics. This paper envisions how learner agency can be performative in the discursive space of a secondary classroom. The research disrupts the notion of a unified subject, a key tenet of sovereign theory that is evident in conceptions of the 'self-regulated', 'self-motivated', 'self-efficacious' student. Drawing on the work of Judith Butler and Bronwyn Davies, the classroom relations in this study are read as both dynamic and interdiscursive. Agency plays out through learners' discourse moves as they act upon and blend discourses to learn in a New Zealand Year 9 science classroom.